Pengaruh Tekanan Operasi dan Bahan Baku pada Unit Pengolah Air Minum Berbasis Single Membran Goldy ULP 2012-100G - Nur Shafa, Annisa; Yuniar; Muhammad Yerizam (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The demand for high-quality and safe drinking water continues to increase in line with population growth and limited clean water sources. This study aims to analyze the effect of operating pressure and raw water sources (PDAM water and Sukomoro water) on the quality of drinking water produced by the Reverse Osmosis (RO) process using the Goldy ULP-2012-100G membrane. The research was conducted at the Energy Engineering Laboratory of Politeknik Negeri Sriwijaya over a period of six months, using pressure variations ranging from 3 to 7 bar. The parameters analyzed included TDS, pH, permeate flux, and rejection efficiency. The results showed that increasing operating pressure positively affected TDS removal efficiency, permeate flux, and pH improvement. The optimal pressure was found at 6 bar, achieving a 95% rejection rate and the highest permeate flux. PDAM water yielded more stable results compared to Sukomoro water, which showed fluctuations in the second trial, possibly due to fouling. The treated water from both sources met the drinking water quality standards based on the Indonesian Ministry of Health Regulation No. 492 of 2010 and No. 2 of 2023. This study confirms that the RO system using the Goldy ULP-2012-100G membrane can effectively process various raw water sources into potable water, with the best efficiency achieved at 6 bar of operating pressure.